Prospective teachers’ iceberg designs in realistic mathematics education approach: Connecting mathematics and the SDGs - Sari, Yurizka Melia; Fiangga, Shofan; El Milla, Yulia Izza; Shahrill, Masitah; Yanti, Liza Puspita (Journal on Mathematics Education, 2025)
The Iceberg Design framework has been utilized to represent the progression of students’ mathematical understanding, moving from informal, contextually grounded reasoning toward formal mathematical abstraction. This study investigates how prospective mathematics teachers develop Iceberg Designs within the Realistic Mathematics Education (RME) framework, a model that enhances contextual learning and supports mathematical literacy. Thirty prospective mathematics teachers from Universitas Negeri Surabaya participated in this qualitative study, collaboratively designing Iceberg models as part of their coursework. Data from document analysis, interviews, and observations were evaluated using content analysis, the research evaluated the depth and coherence of their designs across four key components: situational contexts which evaluates the relevance and variety of real-world situations, model-of representations which examines the assistance of mathematical representation to connect the context into mathematical concept, model-for abstractions which assess the use of mathematical models toward formalization, and formal mathematical concepts which assess the mathematical ideas being explicitly involved. The findings reveal significant variation in the quality and completeness of the Iceberg Designs. Models for equivalent ratios and quadratic equations exhibited strong integration, using multiple, varied contexts to bridge situational and formal mathematical understanding effectively. Conversely, designs for fraction multiplication and quadrilateral area conservation were often surface level, relying on a single, underdeveloped context that hindered abstraction. Importantly, the study underscores the potential of Iceberg Designs to support the Sustainable Development Goals (SDGs), particularly in fostering critical thinking, practical problem-solving, and meaningful contextual learning for high quality of education (SDG 4) and decent work for sustainable economic growth (SDG 8). These insights indicate the need for deeper integration of RME principles in teacher education and curriculum development through sustained investment in this area.